APLIKASI SISTEM INFORMASI PENGENDALIAN DAN MONITORING PENJUALAN BERBASIS WEB PADA PT. SUSAN PHOTO ALBUM (Information Technology and Telematics, 2014)
Abstract : Susan Photo Album is a manufacturing company that started production in 1964 in Semarang. The company started by producing wedding and wedding photo albums are made by hand made of high quality, then evolved to produce wedding book, stationery, corporate premium packaging, premium cards. The purpose of making this information system is to build a System for Control and Monitoring Sales Information based web on PT.SusanPhoto Album. The success of the manufacturing information system control and monitoring of web-based sales at PT. Susan Photo Album on the mark in the absence of which means that the stock minus the existing stock is in conformity with the stock in the information system (computer). Yahoo Messenger With the facility to facilitate communication between sales and sales to consumers and sales with the company. Keywords: Control and monitoring of sales, web-based information systems, susan photo album.